Aspectos teóricos sobre o comércio internacional e dois estudos empíricos para a balança comercial brasileira de bens e serviços não-fatores (SBCA) - Fernando Simoes Azevedo (2007)
This thesis is intended to contribute for a better understanding of the Brazilian trade balance evolution for goods and services (SBCA), due to the importance of this aggregate in the external restrictions to national development. David Ricardos perceptions on foreign trade are taken as the main theory to explain the economic relations in international trade. The theory of spatial income, through Lemos (1988) approach, is also used in order to obtain the theoretical transposition from the agrarian income of Ricardo (situated in the 18th century) to the contemporary urban environment. This theoretical base is then submitted to empirical tests by two different econometric methods: instrumental variables and vector autoregression (VAR). In the first we used annual data from 1947 to 2003 while in the second quarterly data from 1980 to 2005 were employed. The work also discusses the problem of unit roots and structural breaks in time series, key point for the definition of the econometric methods adopted here. In both studies, strong evidence of the evaluated relation was found: the SBCA seems to be explained in some measure by price competitiveness (relative prices) and by internal and external economic activity levels. Besides that, causal relations seem to last for significantly long periods.